Linear and Nonlinear Polarization Syntheses and Their Programmable Controls based on Anisotropic Time‐Domain Digital Coding Metasurface. Issue 1 (16th November 2020) - Ke, Jun Chen; Dai, Jun Yan; Chen, Ming Zheng; Wang, Li; Zhang, Cheng; Tang, Wankai; Yang, Jin; Liu, Wei; Li, Xin; Lu, Yunfeng; Cheng, Qiang; Jin, Shi; et al.
Abstract : Spatial polarization converter can shift the polarization state of incident wave to another state in a specific frequency band. The traditional polarization conversion devices mainly include natural materials and artificial electromagnetic (EM) structures, which are generally sensitive to the incident polarization states and cannot realize polarization manipulations of nonlinear harmonics. These drawbacks limit their developments in wireless communications and radar detection applications. Herein, a general polarization regulation scheme based on anisotropic time‐domain digital coding metasurface is proposed that can achieve both linear and nonlinear polarization syntheses and realize their programmable controls in real time. In this scheme, a nonlinear modulation theory into the polarization conversion methods is integrated, and thus, the scope of the polarization regulation is expanded. An anisotropic time‐domain digital coding metasurface is designed and fabricated to validate the feasibility of the proposed scheme. Theoretical predictions have good agreements with the experiments. The results of this study are expected to promote the developments of space‐time‐polarization regulations and provide efficient approaches for precise EM detections. Abstract : A general polarization regulation scheme is proposed to achieve both linear and nonlinear polarization syntheses and realize their programmable controls in real time, which is based on the anisotropic time‐domain digital coding metasurface. Both theoretical predictions and experiments are in good agreements. This study can promote the developments of space‐time‐polarization regulations and provide efficient approaches for precise electromagnetic (EM) detections.